Strategic analysis of richeese factory in business competition: SWOT analysis - Afifah, Nisa Intan; Sandrina, Sandrina; Agustina, Nabilah; Wahyudi, Wahyudi; Alfarizi, Abdul Wahid (Jurnal Mantik, 2024)
The development of the business world will create opportunities for the food industry, especially in Indonesia, where the number of fast-food restaurants makes competition tighter. Richeese Factory is the only fast-food restaurant with superior product innovation, namely fried chicken covered in hot sauce with cheese sauce. This research aims to study strategies for overcoming business competition by understanding consumer behavior in purchasing decisions for a product. Companies need to pay attention to consumer behavior and other factors. With the influence of price and product quality on purchasing decisions made by consumers, restaurants need to develop the right business strategy to reduce competition. This study uses a qualitative method with SWOT Analysis to make business decisions and determine business strategies. Based on the results of the SWOT Analysis, eleven alternative strategies were formulated, including increasing innovation in products, collaboration and sponsorship, branch expansion, focusing on quality, providing healthy menu options, negotiating with raw material suppliers, responding to responses from consumers well and quickly, displaying menu features that can attract consumer attention, providing healthy drinks. These alternative raw material suppliers offer more competitive prices, offering added value commensurate with price and making product packaging more attractive